2018
DOI: 10.3389/fpsyt.2018.00308
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Anxiety and Depressive Symptoms in Pulmonary Tuberculosis Patients With and Without Tracheobronchial Tuberculosis

Abstract: Background and Objective: Anxiety/depression and tuberculosis are global public health problems. The incidence of psychiatric morbidities is high among tuberculosis patients. However, little is known about the prevalence of anxiety and depression among Chinese pulmonary tuberculosis (PTB) patients, especially those with tracheobronchial tuberculosis (TBTB). The goal of the present study was to explore the prevalence of and associated factors of anxiety and depressive symptoms among PTB patients with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
4
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
8
35
4
5
Order By: Relevance
“…Approximately 26 % of enrolled TB patients had PHQ-9 scores indicative of moderate to severe depression and 15 % indicative of suicidal ideation. Our estimate was comparable to recent studies in several countries that examined depression (moderate to severe) among TB patients, including Ethiopia (17•6-54•0 %) (32)(33)(34) , South Africa (32•9 %) (13) , Angola (49•4 %) (35) and China (18•1 %) (36) . They were, however, considerably lower than those found in Ethiopia using PHQ-9 by Ambaw et al (32) ; these differences may have arisen from variations in study location and population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Approximately 26 % of enrolled TB patients had PHQ-9 scores indicative of moderate to severe depression and 15 % indicative of suicidal ideation. Our estimate was comparable to recent studies in several countries that examined depression (moderate to severe) among TB patients, including Ethiopia (17•6-54•0 %) (32)(33)(34) , South Africa (32•9 %) (13) , Angola (49•4 %) (35) and China (18•1 %) (36) . They were, however, considerably lower than those found in Ethiopia using PHQ-9 by Ambaw et al (32) ; these differences may have arisen from variations in study location and population.…”
Section: Discussionsupporting
confidence: 87%
“…Approximately 46 % of our participants reported anxiety symptoms, comparable with published estimates of other settings: Ethiopia (41•5 %) (34) , Angola (38•3 %) (35) and China (18•4 %) (36) . None of those studies utilised the ZUNG scale; instead, Generalized Anxiety Disorder Questionnaire and Hospital Anxiety and Depression Scale were used to assess the presence of anxiety symptoms, which might be an explanation for the discrepant results.…”
Section: Discussionsupporting
confidence: 87%
“…The characteristics of the study populations included in this study are depicted in Table 1. Out of 25 studies included in the review, seven were from Pakistan [15,[26][27][28][29][30][31], seven from India [32][33][34][35][36][37][38], three from Nigeria [18,39,40], four from Ethiopia [11,19,41,42], one from Brazil [43], one from China [44], one from Cameron [45], and one from Turkey [47]. The studies included in this review were published between 2006 and 2019, with the sample size ranging between 45 participants in India and 1252 participants in China.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Such risk factors include marital status, namely divorce; dyspnea and other clinical symptoms of pulmonary tuberculosis (PTB) or other chronic respiratory diseases; social pressures or stigma following a diagnosis of TB among young individuals; low income; and smoking history . Interestingly, it is unclear whether or not alcohol consumption is a risk factor for depression in TB . However, no risk factors specific to TB that are associated with comorbid depression have been identified in patients with TB .…”
Section: Association Between Depression and Tbmentioning
confidence: 99%
“…17,30 Interestingly, it is unclear whether or not alcohol consumption is a risk factor for depression in TB. 31,32 However, no risk factors specific to TB that are associated with comorbid depression have been identified in patients with TB. 19,33 A prospective controlled trial in India found that psychological intervention significantly improved compliance of anti-TB treatment.…”
Section: Risk Factorsmentioning
confidence: 99%